Comparison of Intraoral Bone Regeneration with Iliac and Alveolar BMSCs. (October 2018) - Wang, F.; Zhou, Y.; Zhou, J.; Xu, M.; Zheng, W.; Huang, W.; Zhou, W.; Shen, Y.; Zhao, K.; Wu, Y.; Zou, D.
This study compared the osteogenic potential of bone marrow mesenchymal stem cells (BMSCs) of iliac and alveolar origins (I-BMSCs and Al-BMSCs, respectively), which were transplanted in combination with β tricalcium phosphate (β-TCP) in peri-implant bone defects to investigate the osseointegration between dental implants and tissue-engineered bone in dogs. Specifically, I-BMSCs and Al-BMSCs were cultured, characterized, and seeded on β-TCP and subjected to immunoblotting analyses and alkaline phosphatase activity assays. Subsequently, these cell-seeded scaffolds were implanted into defects that were freshly generated in the mandibular premolar areas of 4 dogs. The defects were covered with β-TCP + Al-BMSCs ( n = 6), β-TCP + I-BMSCs ( n = 6), or β-TCP ( n = 6) or served as the blank control ( n = 6). After healing for 12 wk, the formation and mineralization of new bones were assessed through micro–computed tomographic, histologic, and histomorphometric analyses, and bone-to-implant contacts were measured in the specimens. It was evident that in this large animal model, I-BMSCs and Al-BMSCs manifested similarly strong osteogenic potential, as significantly more new bone was formed in the Al-BMSC and I-BMSC groups than otherwise ( P < 0.01). Therefore, Al-BMSCs are emerging as an efficient alternative for autologous mesenchymal stem cells in regenerative dental and maxillofacial therapies. I-BMSCs, if not restricted in their bioavailability, can also be of great utility in bone tissue–engineering applications.